2018
DOI: 10.1021/acs.jpcb.7b12571
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Counterions on the Hydration Structure of Lanthanide Ions in Dilute Aqueous Solutions

Abstract: A synergic approach combining molecular dynamics (MD) simulations and X-ray absorption spectroscopy (XAS) has been used to investigate diluted (0.1 M) aqueous solutions of two lanthanide ions (Ln), namely, La and Dy, with triflate, nitrate, and bis(trifluoromethylsulfonyl)imide (TfN) as counterions. The different complexing ability of the three anions has been highlighted by the analysis of the MD simulations: TfN does not form inner-sphere complexes, while a small amount of triflate coordinates both the La an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 88 publications
3
31
0
Order By: Relevance
“…In the same trend, a review published by Smirnov et al showed that structural parameters of Mg 2+ hydration are independent of the chemical nature of the anions [79]. Results are also in line with the findings of a combined Molecular Dynamics and EXAFS investigation on the influence of triflate, nitrate and bis(trifluoromethylsulfonyl)imide counterions on the hydration structure of Lanthanide ions [80]. In this study, the presence of counterions in the cation first or second shell was found to change neither the first shell distance nor the symmetry of the hydration complex formed in solution.…”
Section: supporting
confidence: 80%
“…In the same trend, a review published by Smirnov et al showed that structural parameters of Mg 2+ hydration are independent of the chemical nature of the anions [79]. Results are also in line with the findings of a combined Molecular Dynamics and EXAFS investigation on the influence of triflate, nitrate and bis(trifluoromethylsulfonyl)imide counterions on the hydration structure of Lanthanide ions [80]. In this study, the presence of counterions in the cation first or second shell was found to change neither the first shell distance nor the symmetry of the hydration complex formed in solution.…”
Section: supporting
confidence: 80%
“…For the Lu 3+ ion in aqueous solution, the local hydration structure was measured using extended X-ray absorption fine structure (EXAFS) spectroscopy [16,21,22,23,24] and X-ray diffraction [25,26]. The majority of studies agreed with the 8-fold coordination of water molecules grouped around Lu 3+ in square antiprismatic (SAP) geometry.…”
Section: Introductionmentioning
confidence: 95%
“…These variations may be due to the fact that XRD measured concentrated solutions while EXAFS used relatively dilute solutions [16,21]. However, such differences in concentration scale, pose a problem because ion pairs are likely to form in concentrated solutions [26,27,28,29]. Ion association studied on these solutions do not agree on the nature of the ion pairs/complex species formed.…”
Section: Introductionmentioning
confidence: 99%
“…Ar ecent ab initio study [47] shows that this polarisation is dominated by charge-dipole interactions for metal ions in water and that isotropic polarisability is capable of accurately modelling these systems. Migliorati et al [48,49] have recently published pairwise intermolecular-potentialp arametersf or all Ln III with water.B ased on X-ray spectroscopy data, with an on-polarisable force field and rigid water,t he modelsw ere able to accurately reproducet he structuralp roperties of Ln III aquo complexes. Qiao et al [50] also developed a non-polarisable force fieldb ased on CHARMM and compared it to the polarisable force field of Marjolin et al [45] The solvation energiesf or the non-polarisable model werefound to be as accurate as those calculated with explicit polarisation included, suggesting that polarisability is not crucial forag ood quality model.…”
Section: Introductionmentioning
confidence: 99%
“…A recent ab initio study shows that this polarisation is dominated by charge–dipole interactions for metal ions in water and that isotropic polarisability is capable of accurately modelling these systems. Migliorati et al . have recently published pairwise intermolecular‐potential parameters for all Ln III with water.…”
Section: Introductionmentioning
confidence: 99%